2017
DOI: 10.7595/management.fon.2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory values in the process of organizational change: a case study

Abstract: Values have always been perceived as a guide for action at both individual and organizational levels. By showcasing an example of one Serbian company, the paper aims to present how employees and managers’ collective values can be inconsistent and contradictory, as well as the causes and effects of such a state of company’ system of values. The research was conducted by applying a case study method in a Serbian company comprising both qualitative and quantitative research techniques. The company was in the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…On the contrary, we found that low-general-skill occupations using technologies at work are at a higher risk of experiencing contradictions at work because of organisational changes. Earlier research (Janicijevic, 2017) suggests that the values of both the employees and the managers may be contradictory, and this contradiction is caused by radical changes in the environment and in the organisation itself. Therefore, an absence of high professional competence can presumably affect adaptation to organisational changes, which are a natural part of the organisation’s development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, we found that low-general-skill occupations using technologies at work are at a higher risk of experiencing contradictions at work because of organisational changes. Earlier research (Janicijevic, 2017) suggests that the values of both the employees and the managers may be contradictory, and this contradiction is caused by radical changes in the environment and in the organisation itself. Therefore, an absence of high professional competence can presumably affect adaptation to organisational changes, which are a natural part of the organisation’s development.…”
Section: Discussionmentioning
confidence: 99%
“…“Job insecurity in the workplace” (Factor 1) was measured with nine items from the validated research of Janicijevic (2017) (e.g. “Has your workplace undergone major organisational changes in recent years, or is it about to happen?”), Autor (2015) (“Has the way you work with robotics or artificial intelligence, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, there has been an increased interest among the researchers in determining the correlations between the employees' personality, job satisfaction and general work motivation, mainly on the basis that values at both individual and organizational levels have always been perceived as a guide for specific action (Janicijevic, 2017). There are numerous definitions of the concept of personality in the literature.…”
Section: Personality Dimensionsmentioning
confidence: 99%
“…However, defining core activities is not as easy as it seems and cost-cutting single-mindedness can put the outsourcing decision on the wrong track [23]. Values held within the company can also influence the decision, as this is in essence organizational change [24]. Even McIvor is aware of this drawback and in his last phase talks about analysis of relations between organizational units [9].…”
Section: Insourcingmentioning
confidence: 99%